Giải thuật HEURISTIC mờ cân bằng tải trong lưới điện phân phối - Quyen , Huy Ánh; Nguyen, Nhân Bổn; Duong, Thanh Long; Nguyen, Ngọc Phúc Diễm (Journal of Technical Education Science, 2007)
In the operation of a distribution system, transformer and feeder load balancing is important since it can reduce the risk of overloads due to load change or service restoration following a fault. To achieve load balancing, the operators must change configuration of the distribution network by change the open/close states of the switch on distribution feeders. In this paper, the new algorithm based on fuzzy approach with heuristic are proposed to reach the best configuration load balancing in very short time